Gut Microbiota Variation With Short-Term Intake of Ginger Juice on Human Health - Wang, Xiaolong; Zhang, Dan; Jiang, Haiqiang; Zhang, Shuo; Pang, Xiaogang; Gao, Shijie; Zhang, Huimin; Zhang, Shanyu; Xiao, Qiuyue; Chen, Liyuan; Wang, Shengqi; Qi, Dongmei; et al. (Frontiers in Microbiology, 2021)
Ginger, a widely used functional food and food additive, little is known about the effect of ginger juice, which is rich in many healthful agents, on healthy humans or on its relationship with gut microbiota composition variation. The aim of this study was to investigate the changes in the gut microbial communities that occur following the supplementation of fresh ginger-derived juice in healthy adults and its potential associations with function. A crossover intervention study in which 123 healthy subjects (63 men and 60 women) consumed fresh ginger juice from Zingiber officinale Rosc. or sterile 0.9% sodium chloride was conducted. 16S rRNA sequencing analyses were applied to characterize gut microbiota variation. We found that ginger juice intervention increased the species number of intestinal flora. A decreased relative abundance of the Prevotella-to-Bacteroides ratio and pro-inflammatory Ruminococcus_1 and Ruminococcus_2 while a tendency toward an increased Firmicutes-to-Bacteroidetes ratio, Proteobacteria and anti-inflammatory Faecalibacterium were found. When we did not consider gender, we found differences in bacterial diversity both in community evenness and in richness caused by ginger intervention. In fact, there were different changes in bacterial α-diversity induced by the ginger juice in men and women. We identified 19 bacterial genera with significant differences between the control group (women) and ginger group (women) and 15 significant differences between the control group (men) and ginger group (men) at the genus level. Our results showed that short-term intake of ginger juice had substantial effects on the composition and function of gut microbiota in healthy people. Moreover, our findings underscored the importance of analyzing both male and female individuals to investigate the effects of ginger on gut microbiota. Additional studies are necessary to confirm these findings.